Work-related stress is associated with impaired neuropsychological test performance: a clinical cross-sectional study. (March 2015) - Eskildsen, Anita; Andersen, Lars Peter; Pedersen, Anders Degn; Vandborg, Sanne Kjær; Andersen, Johan Hviid
Abstract Patients on sick leave due to work-related stress often complain about impaired concentration and memory. However, it is undetermined how widespread these impairments are, and which cognitive domains are most long-term stress sensitive. Previous studies show inconsistent results and are difficult to synthesize. The primary aim of this study was to examine whether patients with work-related stress complaints have cognitive impairments compared to a matched control group without stress. Our secondary aim was to examine whether the level of self-reported perceived stress is associated with neuropsychological test performance. We used a broad neuropsychological test battery to assess 59 outpatients with work-related stress complaints (without major depression) and 59 healthy controls. We matched the patients and controls pairwise by sex, age and educational level. Compared to controls, patients generally showed mildly reduced performance across all the measured domains of the neuropsychological test battery. However, only three comparisons reached statistical significance (p < 0.05). Effect sizes (Cohen's d) were generally small to medium. The most pronounced differences between patients and controls were seen on tests of prospective memory, speed and complex working memory. There were no statistical significant associations between self-reported perceived stress level and neuropsychological test performance. In conclusion, we recommend that cognitive functions should be considered when evaluating patients with work-related stress complaints, especially when given advice regarding return to work. Since this study had a cross-sectional design, it is still uncertain whether the impairments are permanent. Further study is required to establish causal links between work-related stress and cognitive deficits.